Montako ja pleonasmi - Branch, Hannele (Virittäjä, 2005)
Monta(ko) how many and pleonasm (englanti) 1/2005 (109) Monta(ko)? how many? and pleonasm The article examines the development of Finnish interrogative expressions denoting amount or measurable quality and marked by the enclitic particle -ko/-k. Since the late nineteenth century, researchers have observed that the effect of this particle in such interrogative expressions is to convey the meaning How X? (e.g. Suuriko? How big?). The number of interrogatives used in this way is limited. Examples are: Montako? How many?; Paljonko? How much?; Kauanko? How long (time)?; Kauasko? (to) How far?; Kaukanako? (at) How far?; and Kaukaako? (from) How far?. Equivalent forms based on certain nominals are also possible, such as Monesko? Which (in an ordinal sequence)?; Vanhako? How old?; and Suuriko?. The article focuses principally on Montako? which, like Paljonko?, occurs in the sixteenth-century texts of Mikael Agricola. The writer cites examples from Finnish dialects, old literary Finnish, Ingrian dialects and Vote (south of the Gulf of Finland), which demonstrate that monta has been used to express not only many but also How much? How many?. The first set of examples in the article consists of sentences used to inquire about the time (Monta(ko) kello on? What is the time? [lit.How much is the time?]), taken from a Finnish geo-linguistic area extending from Vrmland (Sweden) through Finland to Vote areas. The second group of examples consists of interrogative sentences from an area extending from southern Savo (Finland) to Vote areas in which monta has the meaning How many?. The writer suggests that the two sets of examples demonstrate that a word monta meaning How much? How many? has existed in Finnish and is the root of Montako? How many?. Evidence of the existence of Monta? How many? without the particle -ko/-k is provided by examples of old literary Finnish in Gananders dictionary (1787) and, especially, by corresponding forms in Vote. The original absence of the particle -ko/-k is further demonstrated by the interrogatives Paljo? How much? and Mones? Which (in an ordinal sequence)?, both of which appear without the particle in south-eastern Finnish dialects and Vote. Since -ko/-k in these interrogative forms is clearly the Finnish question marker, the article looks at why the interrogative enclitic particle was added to a word which was already in an interrogative form. An examination of pleonasm, both as a normative phenomenon and as a factor causing linguistic change, leads the writer to conclude that Montako? is most likely a pleonastic form which occurred when a reinforcing -ko/-k particle was added. The other interrogatives ending in -ko/-k and expressing amount or measurable quality can be explained as analogical formations. Hannele Branch